Breast cancer [ visual guide for clinicians - Barber, Matthew D.; Dixon, J. M.; Thomas, J. (Visual guide : breast cancer, 2012)
At a time of immense change in all aspects of investigation and management, the guide provides a contemporary and practical account of breast cancer. Carefully selected illustrations are enhanced by concise text, giving the reader a valuable Insight into this vibrant field. This book will serve residents and practitioners well as a quick review of topics in breast cancer. It briefly covers the anatomy and physiology of the breast, the different histologies of breast cancer, and its treatment. The format emphasizes learning from pictures and illustrations, supplemented by text. This will be a useful review for medical professionals taking care of patients with breast disease